Induction of discrete apoptotic pathways by bromo-substituted indirubin derivatives in invasive breast cancer cells - Nicolaou, K.A.a; Liapis, V.b; Evdokiou, A.b; Constantinou, C.c; Magiatis, P.d; Skaltsounis, A.L.d; Koumas, L.e; Costeas, P.A.e; Constantinou, A.I.a (Biochemical and Biophysical Research Communications, 2012)
Indirubin derivatives gained interest in recent years for their anticancer and antimetastatic properties. The objective of the present study was to evaluate and compare the anticancer properties of the two novel bromo-substituted derivatives 6-bromoindirubin-3’-oxime (6BIO) and 7-bromoindirubin-3’-oxime (7BIO) in five different breast cancer cell lines. Cell viability assays identified that 6BIO and 7BIO are most effective in preventing the proliferation of the MDA-MB-231-TXSA breast cancer cell line from a total of five breast cancer cell lined examined. In addition it was found that the two compounds induce apoptosis via different mechanisms. 6BIO induces caspase-dependent programmed cell death through the intrinsic (mitochondrial) caspase-9 pathway. 7BIO up-regulates p21 and promotes G2/M cell cycle arrest which is subsequently followed by the activation of two different apoptotic pathways: (a) a pathway that involves the upregulation of DR4/DR5 and activation of caspase-8 and (b) a caspase independent pathway. In conclusion, this study provides important insights regarding the molecular pathways leading to cell cycle arrest and apoptosis by two indirubin derivatives that can find clinical applications in targeted cancer therapeutics. © 2012 Elsevier Inc.
Keywords: 6 bromoindirubin 3’oxime; 7 bromoindirubin 3’oxime; antineoplastic alkaloid; apoptosis; article; breast cancer; Breast Neoplasms; cancer cell; cancer invasion; cancer patient; caspase 8; caspase 9; cell assay; Cell Cycle; Cell Line; cell viability; controlled study; Female; G2 phase cell cycle checkpoint; human; human cell; Humans; Indoles; M phase cell cycle checkpoint; Neoplasm Invasiveness; Oximes; priority journal; Tumor; unclassified drug; upregulation